Endoscopic management of bile leaks after liver transplantation: An analysis of two high-volume transplant centers. Issue 1 (February 2018) - Sendino, Oriol; Fernández-Simon, Alejandro; Law, Ryan; Abu Dayyeh, Barham; Leise, Michael; Chavez-Rivera, Karina; Cordova, Henry; Colmenero, Jordi; Crespo, Gonzalo; Rodriguez de Miguel, Cristina; Fondevila, Constantino; Llach, Josep; et al.
Background: Bile leak after liver transplantation (LT) is commonly treated with endoscopic retrograde cholangiopancreatography (ERCP); however, there are limited data regarding the optimal treatment strategy. Objective: We aimed to examine the role of ERCP in LT recipients with bile leaks at two large institutions. Methods: We reviewed all ERCPs performed in LT recipients with bile leak and duct-to-duct biliary anastomosis at two high-volume transplant centers. Results: Eighty patients were included. Forty-seven (59%) patients underwent ERCP with plastic stent placement (with or without sphincterotomy) and 33 patients (41%) underwent sphincterotomy alone. Complete resolution was obtained in 94% of the stent group vs. 58% of the sphincterotomy group ( p < 0.01). There was no difference in three-month survival among both groups. Percutaneous transhepatic therapy and surgery were required in 4% and 6% in the stent group vs. 12% and 42% in the sphincterotomy group, respectively ( p = 0.22 and p < 0.001). The only predictive factor of bile leak resolution was stent placement. Conclusion: ERCP with plastic stent placement is highly successful and more effective than sphincterotomy alone for post-LT bile leak treatment. These results indicate that ERCP and plastic stent placement should be considered the standard of care for the treatment of bile leaks in LT.